Positive Compliance Strategies About Covid-19 in @raffinagita1717 Caption Instagram - Irene Pabuntang; Gusnawary Gusnawaty; Kaharruddin Kaharruddin (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana, 2022)
This study aims to determine positive politeness strategies regarding Covid-19 in the Instagram caption @raffinagita1717. The source of the research data is the Instagram caption @raffinagita1717 which discusses Covid-19 by posting from January 1, 2020, to June 30, 2021. The methode of this research is the observation method with the note-taking technique. Listening is done by listening to the Instagram caption @raffinagita1717 which discusses Covid-19. After that, record the speech that has been chosen purposively. The results show that the Instagram caption @raffinagita1717 which discusses Covid-19 uses positive politeness strategies. The research found four forms of positive politeness strategies, namely paying more attention to the interlocutor, using group intimacy markers, involving speakers and interlocutors in activities, and being optimistic. The form of paying more attention to the interlocutor using the form of a directive speech strategy in the form of attention. As for the form of using group intimacy markers, the strategic form is the use of close calls (bun, kawan, dan teman-teman). The form involves the speaker and the interlocutor in the activity using a strategic form of using exclamation points to invite (ayo, yuk, dan mari). Next, be optimistic using the form of a hope marker strategy (semoga dan bismillah)